Clays and Clay Minerals, Vol. 56, No. 5, 531–548, 2008. - Hillier, S.; Pharande, A. L. (The Clay Minerals Society, 2008)
Increasing use of irrigation in India has exacerbated the problems of soil salinity and sodicity. The present study was undertaken on shrink-swell soils from Maharastra State to determine if changes in soil chemistry due to irrigation have affected the clay mineralogy. Twenty six samples (15 locations) of irrigation-induced, saline-sodic, shrink-swell soils and 27 samples (22 locations) of normal un-irrigated (rain-fed) shrink-swell soils were studied using X-ray powder diffraction (XRPD), infrared spectroscopy (FTIR), and scanning and transmission electron microscopy (SEM, TEM). The XRPD analysis of the <0.2 mm fraction of rain-fed, shrink-swell soils indicates a predominance of dioctahedral smectite with minor to trace amounts of kaolinite and chlorite. Traces of palygorskite (1-4%) were detected inthree samples. In contrast, palygorskite is a common component (1-20%) of the fine-clay fraction of salinesodic soils. Quantitative analysis of palygorskite by XRPD in whole-soil (<2 mm) samples showed that saline-sodic soils contain up to 20 wt.% of palygorskite, whereas palygorskite was only detectable (1.5 wt.%) in one sample of the rain-fed set. The SEM, TEM, and FTIR confirm the presence of Fe-rich palygorskite in saline-sodic soils and demonstrate that the fibrous palygorskite crystals are exceedingly small (~0.5 mm long). Delicate palygorskite fibers radiate from the margins of smectite plates suggestive of a pedogenic origin and a close genetic relationship between smectite and palygorskite. The compositions of saturation-paste extracts display a shift from the stability field of smectite in rain-fed soils to that of palygorskite in saline-sodic soils. Thus the occurrence and formation of palygorskite appears to be related to the change in land management from rain-fed to irrigated agriculture. This change has occurred over a period of no more than 40-50 y, implying that palygorskite formation in the irrigated, saline-sodic soils has been an extremely rapid process.
Contemporary Pedogenic Formation Of Palygorskite In Irrigationinduced, Saline-sodic, Shrink-swell Soils Of Maharashtra, India
gsccm56507-hil.pdf - 841KB
Keywords: Periodicals; Geology; Beidellite; Irrigation; Montmorillonite; Palygorskite; Pedogenic; Shrink-swell; Soil; Smectite; Vertisol